Creation and changes in the structure of the Ministry of Sport in Brazil: tensions in space definitions - STAREPRAVO, Fernando Augusto; MEZZADRI, Fernando Marinho; MARCHI JUNIOR, Wanderley (Brazilian journal of physical education and sport, 2015)
This article attempts to revive the process of creating the Ministry of Sport in Brazil and discuss some aspects of conflicting politics of scale present in this policy cycle, which may be related to the reformulation effected by the recent Decree n. 7.529/2011. For this, we use the semi-structured interviews with manager agents of the Ministry of Sport. We argue in particular that the creation of the National Department of Sport, Education, Leisure and Social Inclusion is late reflection of some tensions involving agents from two different parties who have been since 2003 (year of creation of the Ministry) involved in the administration of the Ministry of Sports.